144k views
19 votes
-3(x - 1) + 8 (32 = 3) = x + 7

User ABrowne
by
6.2k points

2 Answers

5 votes
Your correct answer should be 57 I hope this is right
User Crawdingle
by
6.9k points
6 votes

Answer:

Explanation:

First distribute the -3 and the 8

Combine like terms

Move the -3x to the other side by adding 3x to each side

Now move the 7 to the other side by subtracting 7 from each side

Finally, divide both sides by 4 to get x

-3(x-1) + 8(32-3) = x + 7

-3x +3 + 256 - 24 = x + 7

-3x +235 = x + 7

235 = 4x + 7

228 = 4x

57 = x

User Ramin Darvishov
by
5.7k points